Penerapan Model Pembelajaran Tipe Think Pair Share Untuk Meningkatkan Hasil Belajar Ipa Materi Cahaya Dan Sifatnya Pada Siswa Kelas V SD Kristen Patti, Kabupaten Maluku Barat Daya - Gerkora, Priskila E. L.; Pelamonia, Johanes; Souhoka, Renny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the application of the think-pair-share learning model on improving the science learning outcomes of fifth-grade students with the material on light and its properties. The type of research used is classroom action research, with the research subjects being 12 fifth-grade students at Patti Christian Elementary School in Southwest Maluku Regency. The results of the study show that there was an increase in student learning outcomes, as indicated by the achievement of learning completeness in the science subject of light and its properties, namely from 23% in the pre-cycle to 38% in cycle I, then increasing again to 69% in cycle II